Use of an Artificial Neural Network in determination of iron ore pellet bed permeability - Marcelo Chagas; Marcelo Lucas Pereira Machado; João Batista Conti Souza; Eduardo F. de Jesus Frigini (REM: International Engineering Journal)
Abstract The thermal processing of iron ore pellets in pelletizing plants is a decisive stage regarding final product quality and knowledge of its characteristics has a fundamental importance in its process optimization. This study evaluated the variable sensitivity involved in pellet bed formations and their permeability using the artificial neural networks method. The model stated that standard diameter deviation, sphericity and pellet bed height mostly affect bed permeability. The computational model was able to predict pellet bed backpressure by means of pellet geometrical features, thus allowing improving green pellet generation, in order to ensure fuel and energy consumption reduction, final quality improvement and better productivity.